Ixodes ricinus ticks removed from humans in Northern Europe: seasonal pattern of infestation, attachment sites and duration of feeding - Wilhelmsson, Peter (BioMed Central, 2013)
BACKGROUND: The common tick Ixodes ricinus is the main vector in Europe of the tick-borne encephalitis virus and of several species of the Borrelia burgdorferi sensu lato complex, which are the etiological agents of Lyme borreliosis. The risk to contract bites of I. ricinus is dependent on many factors including the behaviour of both ticks and people. The tick’s site of attachment on the human body and the duration of tick attachment may be of clinical importance. Data on I. ricinus ticks, which were found attached to the skin of people, were analysed regarding potentially stage-specific differences in location of attachment sites, duration of tick attachment (= feeding duration), seasonal and geographical distribution of tick infestation in relation to age and gender of the tick-infested hosts. METHODS: During 2008–2009, 1770 tick-bitten persons from Sweden and the Åland Islands removed 2110 I. ricinus ticks. Participants provided information about the date of tick detection and location on their body of each attached tick. Ticks were identified to species and developmental stage. The feeding duration of each nymph and adult female tick was microscopically estimated based on the scutal and the coxal index. RESULTS: In 2008, participants were tick-bitten from mid-May to mid-October and in 2009 from early April to early November. The infestation pattern of the nymphs was bimodal whereas that of the adult female ticks was unimodal with a peak in late summer. Tick attachment site on the human body was associated with stage of the tick and gender of the human host. Site of attachment seemed to influence the duration of tick feeding. Overall, 63% of nymphs and adult female ticks were detected and removed more than 24 hours after attachment. Older persons, compared to younger ones, and men, compared to women, removed “their” ticks after a longer period of tick attachment. CONCLUSIONS: The infestation behaviour of the different tick stages concerning where on the host’s body the ticks generally will attach and when such ticks generally will be detected and removed in relation to host age and gender, should be of value for the development of prophylactic methods against tick infestation and to provide relevant advice to people on how to avoid or reduce the risk of tick infestation.